Assessment of Depression among IBD patients in Gastroenterology and Hepatology Specialized Hospital, Medical City, Iraq using the PHQ-9 - Al-Raeai, Hani Gh.; Kh. Hasan , Hadeer; A. Abdulameer, Zainab; Hamad, Qusay Y.. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: The management of patients with inflammatory bowel disease (IBD) must take mental health into account because it might be difficult to find the best therapies and mental health resources. Anxiety and depression are the two psychological illnesses that IBD patients experience most frequently. The growing incidence of these mental illnesses encourages mental screening of every IBD patient at the initial session. There are easy-to-use, scientifically effective screening techniques for mental health issues. As important as or even more so than a therapy modality may be psychological techniques. Objective: To assess the level of depression among IBD patients in the Gastroenterology and Hepatology Specialized Hospital, Medical City, Ministry of Health and Environment. Patients and methods: The patients were provided with the three-page Patient Health Questionnaire (PHQ) as a self-administrated tool to learn more about their health. When completed, the doctor scans the completed questionnaire, verifies the "yes" responses, and then applies the diagnostic algorithms, which are briefly listed at the bottom of each page. This study was conducted on 98 patients with IBD attending the Gastroenterology and Hepatology Specialized Hospital, Medical City, Baghdad during the period from January – June 2022. Results: Of the total number of cases included in the study 47 (47.9%) were females and 51 (52.1%) were males. The highest frequency was for young adults, 48 cases (49%), and the lowest was for children, 9 (9.2%). There were 43 cases with Ulcerative Colitis and 55 with Crohn’s disease. According to the PHQ-9 score, 26 cases (26.5%) had mild scores and 9 (9.2%) cases had severe scores. The highest frequency of PHQ-9 scores was in the moderately severe range with 44 (44.9%). Conclusion: Mild and moderate levels of depression were the most prevalent among IBD patients across all age and sex groups, which should encourage physicians to address the mental health status of their patients and to include mental health care in the routine checkup of their patients. Received: Feb, 2023 Accepted: Oct, 2023 Published: Jan.2024